THE EFFECT OF OCCUPATIONAL WORK SAFETYAND HEALTH PROGRAM, AND MOTIVATION ON EMPLOYEE’S PRODUCTIVITY AAT HOTEL THE PARK LANE JAKARTA - Dadang Hermawan; Parlagutan Silitonga (Human Capital Development, 2016)
Purpose- The purpose of this study was to analyze the influence of work occupational Health and Safety program, work Motivation on Employees’s Productivity in The Park Lane Jakarta Design/methology/approach- The research method used by distributing questionnaire to 88 respondents of employee of The Park Lane Hotel Jakarta Findings-.The results in this study stated that the Occupational Health, Safety(OHS), and Motivation have individually and simultaneously effected Employees work productivity. The individual effects in weak category when it is tested individually by coefficient of coorelation and determinant. On the other hand, the variables have effected work productivity when it is done simultaneously. Research limitations- Limitation in this research is the absence of financial report for at least, the past three years in a row. These reports are useful to coorelate between the findings and the financial benefit to the company. The financial ratios are useful to meaure the coorelation of the human capital policy against profitability of the Park Lane Hotel Practical implications- Occupational Health and Safety program and work motivation also have simultaneously significantly on the Employee Productivity,provide that information and training are taking place on the importance of personal protective eqquipment.